Correspondence : Health-Care Worker Mortality and the Legacy of the Ebola Epidemic - Evans, David K. (Elsevier, 2015)
The authors modelled how the loss of health-care workers—defined here as doctors, nurses, and midwives—to Ebola might affect maternal, infant, and under-5 mortality in Guinea, Liberia, and Sierra Leone, with the aim of characterising the order of magnitude of likely effects, not providing specific predictions. The authors combined data on: (1) health-care worker deaths from Ebola; (2) the stock of health-care workers pre-Ebola; (3) maternal, infant, and under-5 mortality rates for each country, pre-Ebola; and (4) coefficients of health-care worker mortality, which capture the relation between health-care workers in a given country and different mortality rates (ie, maternal, infant, and under-5 mortality).